Perawatan Stoma pada Bayi dengan Malformasi Anorektal Letak Tinggi tanpa Fistula di Ruang Neonatal Intensive Care Unit : Studi Kasus - Asmira; Fransisca Lio; Sri Deviyanti; Kadek Ayu Erika; Nur Fadilah; Irmayanti (Journal of Bionursing, 2022)
Anorectal malformation without fistula is a congenital disorder that requires a colostomy. Stoma care is very important to prevent infection in neonates, with good care it is hoped that there will be no damage to the integrity of the skin area around the stoma. This study was to report changes in skin color around the stoma in infants with high anorectal malformations without fistulas in the Neonatal Intensive Care Unit (NICU) after stoma treatment. Using a case study design by describing the nursing care given to baby S with a gestational age of 38 weeks in a level III A NICU room at Dr. Wahidin Sudirohusodo Hospital Makassar. Data were collected through observation and documentation of stoma care twice at an 8-day interval. Presentation of data using narrative in explaining the results obtained from case studies After the stoma treatment, the skin color appears reddish, and there is no necrotic. Interventions performed on infants with colostomy are stoma care to prevent damage to skin integrity. On were the first observation before the stoma treatment, the skin color around the stoma was brownish and there was necrotic then, after the stoma treatment, the skin color appeared reddish, there was no necrotic. In conclusion, changes in the skin color of the area around the stoma improved after treatment, the patient's stoma appeared to change from brown and there was necrotic to reddish color and no necrotic.